A synthetic biochemistry platform for cell free production of monoterpenes from glucose - Tyler P. Korman (Nature Portfolio, 2017)
Terpenes are bioactive natural products derived from plants with several commercial applications. Here, the authors engineer a cell-free system composed of 27 enzymes that convert glucose into terpenes, highlighting the potential of synthetic biochemistry approaches for biocompounds production.